Islamic ethic in online business / Norhidayah Ali ... [et al.] - Ali, Norhidayah; Abu Bakar, Suhaida; Ismail, Marhapizah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Business activities have been part of Islam throughout the history and are part of the Islamic field of Muamalah. Nowadays, with the rapid development of internet technology, online business has become the most vibrant medium for conducting business transactions whereby searching for information, ordering products and services, as well as making payments can be done from anywhere and at anytime. Consumers nowadays can access virtually anything at the tips of their fingers. Online business has proven to be convenient, easy and time saving. However, there are some constraints and weaknesses in online business affairs such as fraud, malpractice and misrepresentations. Hence, this study was conducted to explain some of the Islamic ethical guidelines for today’s online business. The method of analysis is by gathering information on the current types of today’s online business and reviewing past literatures. Based on the literature reviews, the study found that one of the major issues among the consumers is on the shariah aspect of the online business. Thus, the study is undertaken to perform further research on the business process of shariah-compliant online business.